2004
DOI: 10.1519/00124278-200411000-00019
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Multiple-Load Training on the Force-Velocity Relationship

Abstract: Toji, H., and M. Kaneko. Effect of multiple-load training on the force-velocity relationship. J. Strength Cond. Res. 18(4):792-795. 2004.-The effect of training with a combination of different loads (multiple-load training) on the force-velocity and force-power relationships was examined with training programs that included maximal isometric contraction (Fmax) and concentric contraction of the elbow flexor muscles. Twenty-one male college students were placed into 3 equal training groups (G 30 ϩ 60 , G 30 ϩ 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 8 publications
3
14
0
Order By: Relevance
“…Therefore, the data can be used to design training programmes for these athletes based on optimal load (2,3,17,18,25,26,32,33,43), as well as knowing how PPO, VGRF and BV will be affected when training across a range of loads, as has been recommended by others (9,41,42). The analysis also demonstrated the value in using data interpolation 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 techniques across this range to complete the profiles (16,23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the data can be used to design training programmes for these athletes based on optimal load (2,3,17,18,25,26,32,33,43), as well as knowing how PPO, VGRF and BV will be affected when training across a range of loads, as has been recommended by others (9,41,42). The analysis also demonstrated the value in using data interpolation 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 techniques across this range to complete the profiles (16,23).…”
Section: Discussionmentioning
confidence: 99%
“…training at a range of loads and velocities encountered during sports performance (9,41,42). For jump squats, an explosive triple-extension exercise that elicits high power outputs, loads ranging from body mass (BM) to as high as 80% of POWER, FORCE & VELOCITY DURING JUMP SQUATS 4 1-RM (2,4,9,17,25,30,31,37,39,40,43) have been identified as optimal for PPO, with an even greater range when Olympic lifts (15,27,28,31) and upper-body ballistic exercises are included (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…Testing of the force, velocity, and power during elbow flexion was performed using a Wilkie's arm ergometer (Toji and Kaneko, 2004). As shown in Figure 1, in a seated position, the subject placed his right upper arm on a table and flexed the elbow joint from 40°to 140°with maximum effort.…”
Section: Methodsmentioning
confidence: 99%
“…This will change the load-power relationship and accordingly the external load that maximizes mechanical power. Previous studies showed load specificity in the adaptations observed on the force-velocity curve with the greatest increases observed at the portion of the curve with the loads used during training (6,19,23). However, different results were observed in relatively weak individuals (7).…”
Section: Introductionmentioning
confidence: 91%